POWER DYNAMICS AND REPRESENTATION IN COETZEE’S WAITING FOR THE BARBARIANS (Contemporary Journal of Social Science Review, 2024)
This paper deals with the intricate exploration of power dynamics, representation, and historical contexts within J.M. Coetzee’s novel Waiting for the Barbarians, employing a subaltern lens to scrutinize the marginalized perspectives. The study investigates the characters’ interactions in oppressive systems, with a focus on the Magistrate’s role in challenging dominant ideologies. Coetzee’s construction of colonial narratives, especially in relation to novel is examined through a postcolonial framework. Ethical dilemmas faced by characters, coupled with literary analysis, contribute to a nuanced understanding of themes. Thus, the aim of study is to ensure a concentrated examination of the selected work. This research significantly contributes to postcolonial discourse, offering insights into the impact of historical contexts on literature and the enduring relevance of power dynamics and representation in contemporary discussion.